2014
DOI: 10.5812/asjsm.23809
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Electronic Personal Health Record for Professional Iranian Athletes

Abstract: Background:By providing sports organizations with electronic records and instruments that can be accessed at any time or place, specialized care can be offered to athletes regardless of injury location, and this makes the follow-up from first aid through to full recovery more efficient.Objectives:The aim of this study was to develop an electronic personal health record for professional Iranian athletes.Patients and Methods:First, a comparative study was carried out on the types of professional athletes’existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Based on participants’ perspective, a number of clinical data elements such as main complaint, primary diagnosis, diagnosis during treatment, physician orders, and patient’s and family history must be recorded and communicated to the national electronic health record. These findings are consistent with the results of previous studies [14, 30, 3840]. Although these studies proposed minimum data sets similar to our results, collecting these data in Iran is mostly limited to the paper and electronic records of patients in hospitals, and are not recorded and communicated to SEPAS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on participants’ perspective, a number of clinical data elements such as main complaint, primary diagnosis, diagnosis during treatment, physician orders, and patient’s and family history must be recorded and communicated to the national electronic health record. These findings are consistent with the results of previous studies [14, 30, 3840]. Although these studies proposed minimum data sets similar to our results, collecting these data in Iran is mostly limited to the paper and electronic records of patients in hospitals, and are not recorded and communicated to SEPAS.…”
Section: Discussionsupporting
confidence: 93%
“…Results of this study, identified information concerning specific patient conditions such as pregnancy, lactation and existence of artificial limbs in patient body as mandatory data elements while, information about patient diet was identified as an unnecessary element. Contrary to these findings, the results of Abdolkhani’s study [38] showed that diet and food allergies should be available in athletes EHR. A reason for this inconsistency is that the diet of all athletes should be monitored routinely regardless of their health condition.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The main impact of implementing a national health data centre was improving management, efficiency, speed and the quality of healthcare as well as reducing costs (Löhr et al, 2010; Seddon and Currie, 2013; Weng et al, 2016). In other studies, the most important impact of developing personal health records was found to be saving costs, improving quality of healthcare (Abdolkhani et al, 2014; Ford et al, 2016) and increasing efficiency (Zhou et al, 2015). As the results show, each technology may have a different impact and it is important for the policymakers to know these details to ensure they plan for outcomes that they really want in the health sector.…”
Section: Discussionmentioning
confidence: 93%
“…In the registration phase, the objective is to design and develop a form for the registration of the runner's electronic personal health record [46] which is the medical history of runners supporting the field doctors in any serious cases of emergency. After that, we developed a web-based registration application and a health database for prevention and assistance in the case runners encounter an incident during the race.…”
Section: 1mentioning
confidence: 99%